The Importance of Understanding Student Development in Increasing Student Interest in Learning - Andi Tenri Ampa; Darmawati A; Abdul Wahab; Andi Tonra Lipu (International Journal of Education, Vocational and Social Science, 2024)
This research aims to find out a general picture of the importance of understanding student development in increasing student interest in learning. This research is qualitative research which aims to describe the understanding of the class teacher at SD Inpres Bontoloe. The subjects in this research were the homeroom teachers who were class IV educators at SD Inpres Bontoloe. The research results obtained are 1) Educators' communication skills in developing interest in learning at SD Inpres Bontoloe, namely the use of good language that is easy for students to understand. 2) Students' ability to communicate increases interest in learning at SD Inpres Bontoloe